Advances of Bioinformatics Applied to Development and Evaluation of Boron-Containing Compounds - Andrade-Jorge, Erik; Garcia-Avila, Ana K.; Ocampo-Nestor, Ana L.; Trujillo-Ferrara, Jose G.; Soriano-Ursua, Marvin A. (Current Organic Chemistry, 2018)
Background: In the last few decades, research into boron-containing compounds (BCCs) has notably increased in medicinal chemistry. Multiple maladies are now targeted by means of BCCs. Since bioinformatics tools have become a common and efficient methodology for drug design and materials science, their application to the study of BCCs is expected to intensify. Objective: This review compiles the use of computational technology to elucidate the chemical-biological effects of BCCs, whether coming from natural sources or drug development strategies. Results: A broad range of computational approaches facilitate pharmacochemical analysis of BCCs. The most focusing on the essential parameters of a boron atom, the reasons for an experimental event, and the shared pharmacodynamics, pharmacokinetics or toxic effects of components of a group of BCCs. Conclusions: Some studies have examined the properties of the boron atom in molecules for designing drugs and biomaterials, others have been aimed to identify the best quantitative structure-activity relationship for a specific target, but lacking some experimental and theoretical data limit the use of boron in theoretical assays. A final remark is made as to the potential impact on BCC research that could result from advances in bioinformatics.
Keywords: drug design